2004
DOI: 10.1097/01.pec.0000133611.42699.08
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Influence of Hospital-Trained, Ad Hoc, and Telephone Interpreters on Perceived Satisfaction of Limited English-Proficient Parents Presenting to a Pediatric Emergency Department

Abstract: Hospital-trained interpreters are a valuable and needed resource to facilitate communication with limited English-proficient patients and families. Other interpretation services are useful but have limitations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 14 publications
1
77
0
4
Order By: Relevance
“…Physicians aware of the impact of language should attempt to be both patient and flexible in adjusting to the process of providing health care to patients by using an interpreter. It is well established in the literature that the use of professional interpreters is a useful tool in health communication to improve the quality of care and overall provider-patient satisfaction [19,68]. Culturally-appropriate interpreter services might reduce the differences in views and beliefs in health care services and build trusting relationships between the physician and the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Physicians aware of the impact of language should attempt to be both patient and flexible in adjusting to the process of providing health care to patients by using an interpreter. It is well established in the literature that the use of professional interpreters is a useful tool in health communication to improve the quality of care and overall provider-patient satisfaction [19,68]. Culturally-appropriate interpreter services might reduce the differences in views and beliefs in health care services and build trusting relationships between the physician and the patient.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Results usually favor RSMI, except when interpretation is done by trained interpreters who are physically present. 10,11 There is some evidence that telephonic interpretation takes longer. 12 Three studies of video interpretation were identified in this literature review.…”
Section: Introductionmentioning
confidence: 97%
“…[17][18][19] However, compared to on-site interpreting, telephone interpreting is often rated lower for interpersonal rapport due to a lack of nonverbal communication and problematic discursive style (e.g., repetition and slowed speech). 9,[20][21][22][23] Providers using videoconference interpreting report less understanding about patients' cultural beliefs than those who use on-site interpreting, 19 making videoconference interpreting a problematic choice when cultural competency is important (e.g., end-of-life care).…”
mentioning
confidence: 99%